1987
DOI: 10.1111/j.1471-4159.1987.tb00949.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Changes in Autopsied Brain Tissue from Cirrhotic Patients with Hepatic Encephalopathy

Abstract: Brain tissue was obtained at autopsy from nine cirrhotic patients dying in hepatic coma and from an equal number of controls, free from neurological, psychiatric, or hepatic diseases, matched for age and time interval from death to freezing of dissected brain samples. Glutamine, glutamate, aspartate, and gamma-aminobutyric acid (GABA) levels were measured in homogenates of cerebral cortex (prefrontal and frontal), caudate nuclei, hypothalamus, cerebellum (cortex and vermis), and medulla oblongata as their o-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
77
0
4

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(93 citation statements)
references
References 22 publications
12
77
0
4
Order By: Relevance
“…Hence, further analyses were performed for 3 combined VOIs: cortex, basal ganglia, and cerebellum. The VOIs were subsequently placed on images of the mean radioactivity concentrations of the second 13 N-ammonia scan and of the 15 O-water scans. Finally, the VOIs were transferred to the respective dynamic images, and time courses of tissue radioactivity concentrations were extracted (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, further analyses were performed for 3 combined VOIs: cortex, basal ganglia, and cerebellum. The VOIs were subsequently placed on images of the mean radioactivity concentrations of the second 13 N-ammonia scan and of the 15 O-water scans. Finally, the VOIs were transferred to the respective dynamic images, and time courses of tissue radioactivity concentrations were extracted (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Before scanning, a short catheter (Artflon, Becton Dickinson, Swindon, UK) was placed percutaneously in a radial artery under local anesthesia. During the 15 O-water scans, arterial blood was sampled by an automated blood sampling system 28 cross-calibrated with the tomograph. Radioactivity concentrations were measured every 0.5 seconds and corrected for external delay and dispersion in the sampling catheter and for radioactive decay to start of the scan.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 In the brain, the predominant route for ammonia metabolism is by glutamine synthesis via the enzyme glutamine synthetase (GS), which is exclusively located in the astrocytes. 3 Consequently, during acute hyperammonemic conditions, brain glutamine levels are increased in HE patients, [4][5][6] which has been suggested as the principal cause leading to astrocyte swelling and cerebral edema. [7][8][9] In vivo studies have shown that administration of methionine sulfoximine (MSO), which specifically inhibits GS, ameliorates astrocyte swelling and brain edema observed during acute hyperammonemia.…”
Section: Introductionmentioning
confidence: 99%